The participation of mentally disabled persons in social life: The analysis of subjective perception - Gevorgianienė, Violeta (Socialinė teorija, empirija, politika ir praktika, 2006)
The concepts or social inclusion, participation of mentally disabled persons in social life are highly discussed in Lithuania. But the persons with mental handicaps are often the objects, not the subjects of these discussions. In the research presented in this article the attempt has been made to evaluate the extent and intensity of social participation from the perspective or mentally disabled persons themselves. The interview method has been used to investigate the perceptions of young mentally retarded individuals of these aspects of social life: social activity and the sense of well being, the personal meaning of the participation, the possibilities and the obstacles of participation, the opportunities to decide for themselves the level of participation, the sense of identity, etc. The research revealed, that mentally disabled persons do feel quite active in the social life in their immediate environment, they often feel as the decision-makers in the context of suggested choices, they describe themselves as being quite happy in their daily lives and connect the feeling of happiness mostly with their competences in different kind of activities, the possibilities to use these competences and with the existence of the social network of very close people (family members, friends, etc.). It has been also found that the value of participation is subjectively measured mostly not by the results of such participation, but by the process of participation itself.